MANAJEMEN KOMUNIKASI DAN INTERPRETASI DIRI SEBAGAI PEMBEKALAN DUNIA KERJA (SMK YADIKA – JAKARTA) - Muzammil, Oktafalia Marisa; Rowena, Janny; Wijaya, Andreas (Universitas Bunda Mulia, 2020)
According to surveyd had been done from (BPS), the number of unemployed people in Indonesia as of August 2018 reaching 7,000,000 people. This figure is equivalent to 5.34% of the total workforce in Indonesia, which is 131,010,000 people. The number of job vacancies always prioritizes the good educational background, the data had been shown: most absorbed graduates are graduate and postgraduate graduates, and professions while the lowest percentage of employment is secondary school graduates. Therefore at this time community services made a theme to providing communication and self-interpretation as a briefing for the world of work will be held in (SMK Yadika - Jakarta). Total sample of 125 students were collected in this session an being divided into two groups in this activity. The method used is the development of Laswell's theory through 5 main stages. The first session will be given direction by the lecturers on communication management starting from the definition, development, and implementation, which is then followed by a role play session. The second session, continued with interviews between students and lecturers. Through this interview session students are given directions on how to communicate well. At the end of the session the students were given one chance to do a review to meet a good interview standard. Based on the results, the participants could see that the students responded actively and enthusiastically in this activity. Keywords: Lasswell Communication Model, Interview Method, Self Interpretation